Non-coding functions of alternative pre-mRNA splicing in development - Mockenhaupt, Stefan (2016)
A majority of messenger RNA precursors (pre-mRNAs) in the higher eukaryotes undergo alternative splicing to generate more than one mature product. By targeting the open reading frame region this process increases diversity of protein isoforms beyond the nominal coding capacity of the genome. However, alternative splicing also frequently controls output levels and spatiotemporal features of cellular and organismal gene expression programs. Here we discuss how these non-coding functions of alternative splicing contribute to development through regulation of mRNA stability, translational efficiency and cellular localization.